Introduction of the American/Asian genotype of Dengue-2 virus into Yucatán state, México (2004)
ABSTRACT: A dengue (DEN) outbreak occurred in the Yucatan State of Mexico in 2002. Three isolates were obtained from patients presenting with DEN-like symptoms, and examined by partial nucleotide sequencing and phylogenetic analysis. The isolates were identified as DEN-2 viruses of the American-Asian genotype; this is the first report of this genotype in the Yucatan State. The DEN-2 viruses of the American-Asian genotype have been associated with more severe disease outcomes. Thus, its introduction into the Yucatan State presents a serious problem to public health authorities. During this outbreak, DEN virus infection was confirmed in 18% (282 of 1,560) of the patients who presented with DEN-like symptoms. Of these, 87 (31%) patients met the World Health Organization criteria for dengue hemorrhagic fever, including two patients who died. The majority (77%) of the patients experienced secondary infections in this epidemic.